Efforts to prove sodomy crime actions taken by civil service police unit and Wilayatul Hisbah in Banda Aceh City - Qolbi, Syifaul (Geuthèë Institute, Aceh, 2025)
Aceh is a province granted authority to implement Jinayat Law (Islamic Criminal Law). This authority is regulated through Aceh Qanun No. 6 of 2014 on Jinayat Law and Qanun No. 7 of 2013 on Jinayat Procedural Law. These provisions authorize the Mahkamah Syar’iyah and the Satuan Polisi Pamong Praja/ Wilayatul Hisbah to handle jarimah such as liwath. However, the absence of comprehensive technical regulations, delays in forensic examinations, and the limited availability of direct witnesses create difficulties in proving cases in accordance with Islamic legal principles and procedural standards. This study employs a normative-empirical juridical approach, utilizing regulatory review, interviews, observations, and documentation. The findings indicate that although law enforcement officers meet the minimum requirement of two valid pieces of evidence, systematic technical obstacles weaken both physical and procedural evidence, thereby posing risks of legal challenges by the parties involved. This research is expected to provide a foundation for drafting clearer technical regulations on the evidentiary process in jarimah liwath cases, strengthen the effectiveness and legitimacy of jinayat law enforcement in Aceh, and serve as a reference for policymakers, law enforcement agencies, and academics in realizing a more just implementation of sharia in the Aceh province.